PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA PUSKESMAS KECAMATAN PESANGGRAHAN JAKARTA SELATAN - Hermansah (Al Hasanah Barokah Foundation, 2024)
This study aims to determine the effect of work discipline and work environment on the performance of Puskesmas Pesanggrahan South Jakarta employees. The research method used is descriptive associative with a total sample population of 64 respondents. Methods of data collection using a questionnaire. The analysis used includes: validity test, reliability test, classical assumption test, correlation coefficient test, coefficient of determination test, simple linear regression test, t-test and F-test. The results of the partial test (t-test) obtained that work discipline and work environment partially have a significant effect on employee performance. The results of the simultaneous test show that discipline affects the performance of the regression equation Y = 17.934 + 0.549X1, the correlation coefficient is 0.613, meaning that the two variables have a strong relationship. The value of determination or contribution of influence is 0.624 or 62.4% the work environment affects the performance of the regression equation Y = 21.127 + 0.465X2, the correlation coefficient of 0.593 means that the two variables have a strong relationship level. The value of determination or contribution of influence is 0.649 or 64.9% work discipline and work environment together have a significant effect on employee performance with a calculated F value > F table or (36.831 > 2.760). This is reinforced by the multiple linear regression equation Y = 18.224 + 0.395X1 + 0.147X2. While the contribution of work discipline and work environment variables to employee performance is 57.6%.